Avaliação in vitro da infiltração apical em canais reobturados com o sistema resilon-epiphany, sob a ação prévia de duas técnicas de desobturação - Botelho, Thereza Cristina Farias (2012)
The purpose of this in vitro study was to compare the quality of apical sealing of refilled root canals using the Resilon/Epiphany system, when previously filled with Gutta-percha in association with two endodontics sealers (Endofill and AH-Plus), as well as compare the same quality sealing using the Resilon/Epiphany system itself, after use of two techniques of material removal. To evaluate the apical leakage, one hundred roots of human teeth were extracted, instrumented and randomly divided into three experimental groups, according to the material chosen for the first filling (Gutta-Percha/Endofill, Gutta-Percha/AH-Plus and Resilon/ Epiphany) and two control groups, positive and negative. After seven days in an oven (37°C, humidity of 100%), each experimental group was randomly subdivided into two subgroups according to the material removal technique (rotary instrumentation associated with chloroform and rotary instrumentation with no chloroform), leading six experimental subgroups. After this, the roots were instrumented again and refilled using Resilon/Epiphany system. After a week, under the same conditions in an oven, the roots were immersed in India ink, centrifuged and cleared. The India ink apical leakage linear measurement, and remaining filling debris on the root canal walls were assessed by NIH ImageJ program. The ANOVA and Tukey tests were used to make the comparison of the apical measurement leakage and the non parametric Kruskal Wallis test to compare the remaining filling debris in the three analyzed thirds and among the material used. The value p<0,05 was considered to be statistically significant. With regard of the presence of leakage, the subgroup 1(Endofill/removal filling technique without solvent) presented the worse linear apical leakage values. However, the subgroup 6(Resilon/Epiphany/removal filling technique with solvent) presented the lowest leakage measurement values. There was no difference between the remaining debris measurements in the three radicular thirds analyzed (p=0,226), but the subgroup filled with Resilon/Epiphany presented the higher amount of debris after the filling material removal without solvent, as well as, roots canals filled and refilled with Resilon/Epiphany, using chloroform, presented the lowest linear apical leakage values when compared with the others.